Effect of particle size and moisture content onbulk density of rice husk pellet as bioenergy - Wan Ahamad, Wan Mohd Aznan; Mohd Yusuff, R.; Abdul Aziz, F.; Mat, Z. (Penerbit MARDI, 2018)
Rice husk (RH) biomass is a by-product from rice mill and has a great potential to be used as an energy feedstock. Nevertheless, the low bulk density (BD), inconsistent moisture content (MC) and large particle size (PS) of the RH have affected its potential applications. Therefore, this study aims to improve the BD of RH via densification method and optimize its MC and PS to produce a quality pellet. The effect of MC of pellet’s compound (12, 16 and 20%) and PS (2, 4 and 6 mm) on the quality of RH pellets were investigated. The range of result for the BD is 610.36 to 687.11 kg/m3. Meanwhile, the results of multiple regression analysis and analysis of variance (ANOVA) have indicated that BD of the RH pellets was significantly influenced by MC of the pellet’s compound. The optimum BD of the RH pellets was represented by a combination of the pellet’s compound at MC 12% & Ground 6 mm. The findings are very useful for production of the RH pellets via densification process (using rotary pellet press) as a bioenergy feedstock.